Where is Bie-Modern Going? Responding to Professors who study Bie-modern Theories - Jianjiang, Wang (Asian Journal of International Affairs, 2021)
“Bie-modern” is a theory about social form. It refers to “doubtful modernity” or pseudo modernity, manifested in the hybridity of the modern, pre-modern and post-modern. At present, Bie-modern theory is applied in philosophy, aesthetics, literature, linguistics, art, design, psychology, tourism, law, economics, and Human-Computer Interaction. Bie-modernism is to seek the direction of future development in the mixed society and to reduce human misjudgments and errors on the way forward. Therefore, it is the priority of Bie-modernism to distinguish between truth and falsehood. Where is Bie-modern going? Firstly, we shall leave the ambiguity of the word “Bie”, to distinguish the difference between Bie-modernism and “plural modernity”, to distinguish true and false modernity, to distinguish the difference between Bie-modernism and modernism and post-modernism. Secondly, towards authenticity, to seek the truth and reality and implement the real modernity. Thirdly, we will be implementing life equity/life stocks, an inherent right to life of every individual, and the share that the right to life holds in the total wealth of society that cannot be deprived, transferred for the whole of their life, that means the right to enjoy free medical care, free education, free old-age pension, and the right to food, clothing, housing, and transportation. To realize human life equity/life stocks, the historical mission of society lies in eliminating the proletariat rather than the bourgeoisie. Life equity/life stocks is a primitive and real right, which is not influenced by acquired ideas and has the most irreplaceable dignity and value of life. Life equity/life stocks are closely related to human well-being and aesthetic feeling, and it has become the source of both. Lastly, we will be upholding “Bie”, the distinguishing, to the end through entering the ideological market and keeping authenticity, implementing life equity/life stocks, and the Great-leap-forward Pause of Bie-modernism. At present, Bie-modernism has rippled in the United States and the European Union. In the future, we will bring it to more countries and regions. The future development of Bie-modernism will focus on returning to the origins and implementing life equity/life stocks.